Improving the safety risk matrix by considering cross-cultural risk perception using HFACS methodology - Chan, Wesley Tsz-Kin; Li, Wen-Chin (Springer, 2026)
This paper addresses the evaluation of safety risks on the basis of probability of occurrence and the severity of potential consequences. Using the Human Factors Analysis and Classification System (HFACS) as a framework, cross-cultural variations in the frequency of occurrences and severity of human factors conditions (as presented in significant ‘routes to failure’) were applied to the Safety Risk Assessment Matrix. Analysis of N = 121 responses highlighted significant cultural differences in safety risk assessments, providing justification for the targeted prioritisation of control actions using safety risk indexes derived from HFACS outputs. The present findings support more directed administration of risk management resources within flight operations, specifically amongst pilots from civilian, airline-sponsored, and ex-military backgrounds. Safety and risk managers can apply the methodology to improve the selection and prioritisation of safety initiatives, offering potential improvements to the relevance and cost-effectiveness of safety risk management endeavours.
Keywords: Artificial Intelligence & Image Processing; 46 Information and computing sciences; Human Factors Analysis and Classification System (HFACS); Safety Risk Matrix; Safety Management Systems